Viral Transport Medium produced for Covid-19 swab samples collection in Nigeria - Muhibi, M.A.1*, Hassan, A.O.2, Moemeke O3, Adebayo, T.O.4, Oyetunji, T.G.5, Moshood, W.K.6, Abiodun, O. 6 (Sokoto Journal of Medical Laboratory Science)
Accuracy in viral diagnosis depends both on the technology employed for the Assay and the medium used for preservation during transportation to the laboratory. SARS CoV-2 virus causes coronal virus disease (COVID-19) and it spreads from an infected person’s mouth or nose in small liquid particles when they cough, sneeze, speak, sing or breathe. Hence, swabs collected from nostril and throat are used for its definite diagnosis, by using molecular technique. The challenge to prepare in-country viral transport medium (VTM) to preserve samples collected for COVID-19 testing starred Nigeria Scientists at the face, when the imported VTMs were exhausted shortly after the pronounced global lock-down in the second quarter of 2020. As a way of responding to this challenge, VTM was produced and validated using amino acid substrates, fungizone, gentamycin and phosphate buffer saline. The products were subjected to sterility test using Chocolate agar and Sabouraud dextrose agar. The following bacteria viz: E. coli, Pseudomonas sp., Bacillus sp., Staphylococcus sp. and Klebsiella sp, were also inoculated into the VTM vials and incubated for 34 consecutive days from which the wire-loop filled inoculums were sub-cultured on Chocolate agar and Sabouraud dextrose agar at 24 hours interval.  No growth was recorded in both situations. Two thousand five hundred vials of the VTM produced were tested in parallel in the NCDC accredited laboratories in Oyo, Lagos, Imo, Ekiti and Osun States; alongside the few imported VTMs in circulation and the performance was 100% the same. This interventional study clearly showed in comparison with imported brands of VTMs, the possibility of using cheap readily sourced materials in low-income setting for the production on in-house VTMs, giving engagement of skillful personnel for the purpose.